Impact of digital economy, productivity, natural resources and innovation capacity on FDI flows in emerging market countries - Chua, Chy Ren; Nanthakumar Loganathan,; Yogeeswari Subramaniam,; Tirta Nugraha Mursitama, (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study aims to examine the effects of digital economy (DE), natural resources (NRs), productivity and innovation capacity on foreign direct investment (FDI) flows in 24 emerging market countries (EMCs) from 2000 to 2021. Heterogeneous panel data estimates were used to analyse short- and long-term relationships between dependent and independent variables. The digital index was constructed using the principal component analysis approach. In terms of short- and long-term relationships, FDI flows, progress in DE, NRs and total factor productivity performance have a positive impact. The significance of indicators for FDI sustainability flows in EMCs is demonstrated by the multidimensional and bidirectional causal relationships between FDI and a few variables. The findings of this study provide a comprehensive empirical figure that can be used to enhance strategies for expanding the flow of FDI in short- and long-term periods, ultimately improving economic sustainability for EMCs.